Short Communication: Variation in vocal cord morphometric characters among dangdut type and the slow type Gaga Chicken - ABINAWANTO ABINAWANTO; ALFI SOPHIAN; PIPIH SUNINGSI EFENDI; TITIN SISWANTINING (Biodiversitas Journal of Biological Diversity, 2018)
Abinawanto, Sophian A, Effendi PS, Siswantining T. 2018. Short Communication: Variation in vocal cord morphometric characters among dangdut type and the slow type Gaga Chicken. Biodiversitas 19: 1902-1905. Gaga chicken is one of the ornamental chicken originating from Sidendreng and Rapang (South Sulawesi). Gaga chicken has a unique crowing sound, like people laugh. Gaga’s chicken which has a long and fast crowing sound known as the dangdut type, while those with short and slow crowing sound are known as slow type. Study was conducted in Pinrang (South Sulawesi), where one of the pure strains are located. Samples were collected from Kanie, Bullo, Macege, Rappang, and Sidenreng. The purpose of study was to determine the characteristics of the vocal cord morphometric among the dangdut type and the slow type of Gaga’s chicken. All of the morphometric data were recorded and analyzed by Mean Test, using SPSS (version 22). The results showed that there was no significant difference (a = 0.010) among the dangdut type and the slow type based on syrinx morphometric. Meanwhile, according to the trachea muscle morphometric the results showed that the trachea muscle of dangdut type was longer than the slow type (a < 0.010). In addition, either the right or the left trachea muscle of dangdut type was longer than either the right or the left trachea muscle of the slow type (a < 0.010).